족관절이 유합되어 있는 상태에서 동측 슬관절 고위경골외반절골술을 시행한 이후 후족부 정렬의 변화: 증례 보고 - 이성산; 서진수; 박경우; 최준영; Sung Sahn Lee; Jin Soo Suh; Kyeong Woo Park; Jun Young Choi (대한족부족관절학회지, 2024)
Ankle arthrodesis was performed on a 55-year-old male patient with an active lifestyle who developed severe arthritis in the left ankle. Over the follow-up period, high tibial valgization osteotomy was conducted for painful medial knee joint arthritis with genu varum deformity to correct overall lower limb alignment from varus to valgus with respect to the fused ankle. This study was conducted to investigate how hindfoot alignment would change when the overall alignment of the lower limb shifted from varus to valgus with the ipsilateral ankle in a fused state. Conclusively, while no intrinsic changes in the hindfoot alignment were observed following the alteration of lower limb alignment, the hindfoot naturally adjusted to valgus deviation in response to limb valgus realignment. Moreover, symptoms changed in line with this adjustment. Given the absence of similar case studies or reports, a review of relevant literature is included to contribute to knowledge of this subject.